AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN WRITING PARAPHRASE AT ENGLISH EDUCATION DEPARTMENT - M. Riskiyadi Siregar (English Literature Department, Adab and Humanities Faculty, 2024)
The aimed of this research to analyze students’ difficulties in writing paraphrase. This research approach was qualitative method with a case study design. There were 28 students from sixth semester as respondent to the questionnaire. Then 6 students were taken randomly to become interview respondent. The findings in this research show that difficult to write content that found, difficult to express own word, finding ideas, have internal problem and lack understanding the word. The other hand, in the writing structures found that, difficult to connect sentences, lack of understanding of writing, lack of ideas and difficulty in changing and processing word. Meanwhile, difficulties in language that, often used the same word or often wasted word. In additional reason difficulties in writing that are language related problem found, difficult to understanding the language. Writing style found that, lack of understanding grammar, difficult to find conjunction, a good writing style, and find synonym. And poor reading comprehension found that, difficult to understand the word, meaning, purpose of the text and difficult to understand the text. It can be concluded that, in writing paraphrase students felt difficult in writing content, structure and the reason why the students felt difficulties in writing paraphrase that are language related problem, writing style and poor reading comprehension.